Alpha-Synuclein Oligomers—Neurotoxic Molecules in Parkinson's Disease and Other Lewy Body Disorders - Ingelsson, Martin (Frontiers in Neuroscience, 2016)
Adverse intra- and extracellular effects of toxic α-synuclein are believed to be central to the pathogenesis in Parkinson’s disease and other disorders with Lewy body pathology in the nervous system. One of the physiological roles of α-synuclein relates to the regulation of neurotransmitter release at the presynapse, although it is still unclear whether this mechanism depends on the action of monomers or smaller oligomers. As for the pathogenicity, accumulating evidence suggest that prefibrillar species, rather than the deposits per se, are responsible for the toxicity in affected cells. In particular, larger oligomers or protofibrils of α-synuclein have been shown to impair protein degradation as well as the function of several organelles, such as the mitochondria and the endoplasmic reticulum. Accumulating evidence further suggest that oligomers/protofibrils may have a toxic effect on the synapse, which may lead to disrupted electrophysiological properties. In addition, recent data indicate that oligomeric α-synuclein species can spread between cells, either as free-floating proteins or via extracellular vesicles, and thereby act as seeds to propagate disease between interconnected brain regions. Taken together, several lines of evidence suggest that α-synuclein have neurotoxic properties and therefore should be an appropriate molecular target for therapeutic intervention in Parkinson’s disease and other disorders with Lewy pathology. In this context, immunotherapy with monoclonal antibodies against α-synuclein oligomers/protofibrils should be a particularly attractive treatment option.